Thriving in Constraints: Exploring the Interplay of Human Capital, Social Capital, and Financial Constraints in Frugal Innovation within Family Businesses - Alumno, Timothy Allan D.; Azurin, Raya Gabriele T.; Dumayas, John Renz I.; Tan, Sherleen G.; Tanpoco, Manuel R.; Caminong, Joliber M. (Future Science / FSH-PH Publications, 2024)
This study aims to learn the impact of human capital, social capital, and financial constraints on frugal innovation as perceived by family businesses in the Philippines. Quantitative research was performed using data collected from 93 family businesses, which were analyzed using simple linear regression and structural equation modeling. The results showed that human capital, social capital, and financial constraints, individually and collectively, have a significant impact on frugal innovation. The results also indicated that all measures used for human capital and financial constraints are acceptable, while some measures of social capital and frugal innovation were deemed unfit and were removed from the model. The academe should expand or improve its discussion and curriculum on frugal innovation and continue to look at this through the lenses of its theoretical and practical aspects. Moreover, professors and students should study the relationship further and ultimately expand knowledge and understanding. Family businesses should prioritize improving their human capital to enhance their frugal innovation capabilities. Implementing efficient financial procedures, investigating alternative funding sources, and actively seeking external finance opportunities are crucial. Moreover, family businesses should develop robust social networks. Lastly, the Philippine government should actively encourage continuous learning through mentorship programs and networks.